Single molecule localization microscopy of the distribution of chromatin using Hoechst and DAPI fluorescent probes - Szczurek, Aleksander; Best, Gerrit; Cremer, Christoph (Nucleus, 2014)
Several approaches have been described to fluorescently label and image DNA and chromatin in situ on the single-molecule level. These superresolution microscopy techniques are based on detecting optically isolated, fluorescently tagged anti-histone antibodies, fluorescently labeled DNA precursor analogs, or fluorescent dyes bound to DNA. Presently they suffer from various drawbacks such as low labeling efficiency or interference with DNA structure. In this report, we demonstrate that DNA minor groove binding dyes, such as Hoechst 33258, Hoechst 33342, and DAPI, can be effectively employed in single molecule localization microscopy (SMLM) with high optical and structural resolution. Upon illumination with low intensity 405 nm light, a small subpopulation of these molecules stochastically undergoes photoconversion from the original blue-emitting form to a green-emitting form. Using a 491 nm laser excitation, fluorescence of these green-emitting, optically isolated molecules was registered until “bleached”. This procedure facilitated substantially the optical isolation and localization of large numbers of individual dye molecules bound to DNA in situ, in nuclei of fixed mammalian cells, or in mitotic chromosomes, and enabled the reconstruction of high-quality DNA density maps. We anticipate that this approach will provide new insights into DNA replication, DNA repair, gene transcription, and other nuclear processes.
Gesehen am 10.08.2020